Virtual and Augmented Reality in Cardiac Surgery - Arian Arjomandi Rad; Robert Vardanyan; Aleksandra Lopuszko; Christina Alt; Ingo Stoffels; Bastian Schmack; Arjang Ruhparwar; Konstantin Zhigalov; Alina Zubarevich; Alexander Weymann (Brazilian Journal of Cardiovascular Surgery, 2021)
Abstract Virtual and augmented reality can be defined as a three-dimensional real-world simulation allowing the user to directly interact with it. Throughout the years, virtual reality has gained great popularity in medicine and is currently being adopted for a wide range of purposes. Due to its dynamic anatomical nature, permanent drive towards decreasing invasiveness, and strive for innovation, cardiac surgery depicts itself as a unique environment for virtual reality. Despite substantial research limitations in cardiac surgery, the current literature has shown great applicability of this technology, and promising opportunities.